Acceptance and Commitment Therapy for adults with head and neck cancer experiencing psychological distress: a hermeneutic single case efficacy design (HSCED) series - Morris, Nicolle (2018)
Background: Individuals with head and neck cancer (HNC) suffer with varying degrees of functional impairment, threats to life and reduced social functioning. They are at an elevated risk of experiencing clinical levels of psychological distress (i.e. anxiety and depression) (Hammerlid & Taft, 2001; Rogers, Ahad, & Murphy, 2007). The cancer-psychotherapy research base largely consists of trials that either regard cancer patients as a homogenous group or focus on patients with the most common cancer sites (e.g., breast). This has resulted in an under-representation of HNC patients (Chong Guan et al., 2016). Acceptance and Commitment Therapy (ACT) has an emerging evidence base for cancer populations (Hulbert-Williams et al, 2015). It is important to test and refine psychotherapy interventions: examining whether effectiveness of ACT extends to those with HNC and – importantly – investigating the processes by which ACT interventions may contribute to positive outcomes (Moyer et al, 2012).